A pyrylium-based colorimetric and fluorimetric chemosensor for the selective detection of lysine in aqueous environment and real sample. Issue 21 (20th May 2015) - Qian, Xiaomin; Gong, Weitao; Wang, Furui; Lin, Yuan; Ning, Guiling
Graphical abstract: Highlights: The synthetic procedures are quite simple, only 3 steps. The exclusive reactivity made this detection selective. The detection process could be observed by naked eye. Abstract: A new chemosensor based on pyrylium salt has been developed. The sensor can selectively fulfill the detection of lysine among 20 common amino acids in aqueous environment and exhibit a distinct color change and 'turn-on' fluorescence. Besides, simple test paper based on this sensor was also presented, which elucidated the feasibility of lysine detection in real samples.